Statistical adjustment of the parameters of multi-objective optimization problems with design expert method - Hasan-Zadeh, Atefeh (Journal of Advanced Computer Science & Technology, 2020)
Optimization methods in which one single criterion is considered cannot provide a comprehensive solution to various decision- making algorithms because they cannot consider the interchange of conflicting goals that sometimes conflict with one another. Multi-objective opti-mization is a suitable solution to this obstacle. Given the importance of multi-objective optimization problems in engineering and technology, adjusting the parameters of these types of problems will, in addition to the decision-making accuracy, facilitate the analysis of the results and makes it more applicable. For this purpose, multi-objective optimization using experimental design methods has been developed which can solve these problems by considering different objectives simultaneously. Mathematical modelling for the setting of the parameters of the considered problem with all the statistical details related to their prediction and optimization have been studied.Â